Unlocking economic opportunities: The Igbo apprenticeship model’s impact on wealth creation in Kano, Nigeria - Nnanguma Kingsley Ahamefula (CV. Literasi Indonesia, 2026)
This study explores the economic significance of the Igbo Apprenticeship Model (IAM) as a wealth creation strategy in Kano City, Kano State, Nigeria, with a focus on its adaptability in a non-Igbo socio-economic setting. The aim is to examine the extent to which IAM contributes to entrepreneurship, employment generation, and wealth accumulation among urban dwellers in Kano. The specific objectives are to evaluate the structure and operations of IAM among Igbo business owners in Kano; measure the economic outcomes of apprentices’ post-graduation; and identify institutional and operational constraints affecting the model. A quantitative-dominant mixed-methods approach was used. Structured questionnaires were administered to 200 former apprentices, complemented by key informant interviews with 30 Igbo mentors (Ogas) across Sabon Gari Market, Singer Market, and Kofar Ruwa Commercial Area. Data were analyzed using SPSS (v25) for descriptive statistics, regression analysis, and thematic coding of qualitative responses. Findings indicate that 82.5% of former apprentices established independent ventures within 18–30 months after graduation. Of these, 67.2% reported monthly profits of ₦150,000–₦450,000, while 54.3% employed between 2–5 workers, demonstrating wealth multiplication effects. Regression analysis revealed a significant positive relationship (R² = 0.61, p < 0.05) between apprenticeship duration and post-graduation business success. Challenges identified include capital scarcity (74%), absence of formal legal backing (62%), and rising cases of broken trust (33%). The study concludes that IAM is an efficient indigenous framework for entrepreneurship and job creation. It recommends policy support, legal recognition, and integration into vocational training programs.